Magnetic resonance imaging in pelvic endometriosis with surgical correlation: a pictorial review - Jindal, Gunjan; Kalpdev, Arun; Shrivastava, Amit; Jain, Simran; Mann, Srishti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Endometriosis is a common gynaecological problem, primarily affecting women of reproductive age. Most common site of endometriosis is ovaries. Extra ovarian sites include uterine ligaments, fallopian tubes, rectosigmoid, laparotomy or C-section scars and urinary bladder. There can be formation of ovarian endometriotic cysts or deep infiltrating endometriosis. The role of MRI is in the evaluation of deep or more complex disease as it enables a large field of view, superior contrast resolution and multiplanar capabilities as compared to ultrasound. In this article, we are describing MRI imaging appearances of endometriomas and deep pelvic endometriosis in the form of a pictorial essay.